Step 1 had the mistake. It should have been (6−4)436.
Step 2 had the mistake. It should have been 32 = 9.
Step 3 had the mistake. It should have been 3−2 = 1−2 = -1.
So, the correct simplified expression is -1.
student simplified this expression: (33⋅ 2−4)436
using these steps:
Step 1: 312 ⋅ 2−1636
Step 2: 36216
Step 3: Answer is 0.011
(1 point)
Responses
Step 1 had the mistake. It should have been (6−4)436
Step 1 had the mistake. It should have been the fraction with numerator open paren 6 to the negative 4 power close paren to the 4th power and denominator 3 to the 6th power
There is no mistake. The answer is correct.
There is no mistake. The answer is correct.
Step 2 had the mistake. It should have been 32 =9
Step 2 had the mistake. It should have been 32 =9
Step 3 had the mistake. It should have been 3−2 = 1−2 = 1
Step 3 had the mistake. It should have been 3−2 = 1−2 = 1
Skip to navigation
page 3 of 3
3 answers
WHAT IS THE CORRECT ANSWER
The correct answer is -1.